THE ECONOMY OF FREE TIME AS A DRIVER FOR THE DEVELOPMENT OF SUCCESSFUL PROJECTS IN TOURISM AND HOSPITALITY - Dzhandzhugazova, Elena A.; Blinova, Ekaterina A.; Stepanova, Svetlana A. ,; Romanova, Marianna M.; Sukhanovskiy, Yuri A. (International Journal of Psychosocial Rehabilitation, 2020)
The article focuses on the urgent problem of the development of free time economy. The problem emerged from the trend of a growing amount of free time available to people who live in developed countries. It has been proved that currently the new economy of many countries is consistently growing due to the creation of new industries which may offer consumers a new product. The main objective of this study is the identification of methodological and practical approaches to get a deeper insight into the problem of enjoying leisure with a focus on its prospective types, i.e. tourism and hospitality. The ways of spending free time preferred by Russian people as identified by the sociological research suggest that cultural and museum products may be considered as new forms of leisure that can satisfy people's needs for self-development and bring profit to regional and municipal budgets. The article shows the experience of the most successful museum projects and addresses matters of determining their efficiency, which include calculating the number of museum visitors and visitors of other hospitality enterprises: hotels, catering and leisure facilities. The content of the article may be useful to the scientific and educational community as well as travel industry businesses who are involved in project-making in the field of tourism and hospitality.